Inclusion in the System of State Preschool Institutions of Serbia from the Parents’ Perspective - Marija Marković (Društvene i Humanističke Studije, 2022)
The realization of inclusive education at the preschool age is an important effort within the school system of a country. It has been established that inclusive education has a stimulating effect on children with disabilities, as well as on typically developing children. Because of this, it is necessary to start with its realization at the preschool age. The paper presents the results of empirical research conducted on a sample of 763 parents of children attending preschool institutions in the territory of eastern and southeastern Serbia, which were collected using an assessment scale specially constructed for this research. Bearing in mind the importance of the formation of positive attitudes of parents as key actors in the upbringing of typically developing children, who should represent to their children a model of adequate behavior towards persons with developmental disabilities, the research aims to examine the attitudes of parents about inclusion in the system of state preschool institutions. It was established that the majority of parents recognize the most significant advantages of inclusion and the prerequisite for achieving inclusion in the context of institutional preschool education. When it comes to obstacles to achieving inclusive education, it was found that parents recognize them to a lesser extent. Also, it was established that there are statistically significant differences in parents' responses to certain items concerning the variables of gender, age, and level of education. The findings of this research can represent a good starting point for improving existing institutional practice in the context of inclusive education.